PENGARUH PENGAWASAN INTERN, PERENCANAAN, DAN PELAKSANAAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KINERJA SKPD PEMERINTAH DAERAH KABUPATEN SIGI - Djiloy, Novita Lerly (Katalogis, 2016)
The Influence of Internal Control, Planning, and The Implementation of regional finance accounting system influence the performance of officials in Sigi Governmental institutions; 2) significant influence of internal control, planning, and the implementation of regional finance accounting system on the performance of officials in Sigi governmental institutions; 3) significant influence of internal control on the performance of Governmental intitutions in Sigi; 4) significant influence of planning on the performance of Governmental institutions in Sigi; 5) significant influence of the implementation of regional finance accounting on the performance of Governmental institutions in Sigi. The study means to verify the relationships of variables by including 42 respondents who selected by census method. The result can be concluded that: 1) internal control, planning, and the implementation of regional finance accounting system simultaneously have significant influence the performance of officials in Sigi governmental institutions; 2) internal control significantly influences the performance; 3) planning has insignificant influence on the performance of officials in Sigi governmental institutions; 4) the implementation of regional finance accounting significantly influences the performance of Governmental institutions in Sigi.